The effect of combined knockdowns of Attacins on survival and bacterial load in Tenebrio molitor - Keshavarz, Maryam; Zanchi, Caroline; Rolff, Jens (Frontiers in Immunology, 2023)
Upon infection, insect hosts simultaneously express a cocktail of antimicrobial peptides (AMPs) which can impede pathogen colonization and increase host fitness. It has been proposed that such a cocktail might be adaptive if the effects of co-expressed AMPs are greater than the sum of individual activities. This could potentially prevent the evolution of bacterial resistance. However, in vivo studies on AMPs in combination are scarce. Attacins are one of the relatively large AMP families, which show anti-Gram-negative activity in vitro. Here, we used RNA interference (RNAi) to silence three members of the Attacin family genes in the mealworm beetle, Tenebrio monitor: (TmAttacin1a (TmAtt1a), TmAttacin1b (TmAtt1b), and TmAttacin2 (TmAtt2) both individually and in combination. We then infected T. molitor with the Gram negative entomopathogen Pseudomonas entomophila. We found that survival of the beetles was only affected by the knockdown of TmAttacin1b, TmAttacin2, and the knockdown of all three Attacins together. Triple knockdown, rather than individual or double knockdowns of AMPs, changes the temporal dynamics of their efficiency in controlling the colonization of P. entomophila in the insect body. More precisely, AMP gene expression influences P. entomophila load early in the infection process, resulting in differences in host survival. Our results highlight the importance of studying AMP-interactions in vivo.